Migration, friendship ties, and cultural assimilation - Facchini, Giovanni; Patacchini, Eleanora; Steinhardt, Max F. (Wiley, 2015)
We study migrants’ assimilation by analyzing whether friendship with natives is a measure of cultural assimilation and by investigating the formation of social ties. Using the German Socio-Economic Panel, we find that migrants with a German friend are more similar to natives than those without along several important dimensions, including concerns about the economy, interest in politics and a host of policy issues. Turning to friendship acquisition, we find that becoming employed, time spent in the host country, the birth of a child, residential mobility and additional education acquired in the host country are significant drivers of social network variation.